Multi-laminate Annulus Fibrosus Repair Scaffold with an Interlamellar Matrix Enhances Impact Resistance, Prevents Herniation and Assists in Restoring Spinal Kinematics - Borem, Ryan (J Mech Behav Biomed Mater, 2019)
Focal defects in the annulus fibrosus (AF) of the intervertebral disc (IVD) arising from herniation have detrimental impacts on the IVD’s mechanical function. Thus, biomimetic-based repair strategies must restore the mechanical integrity of the AF to help support and restore native spinal loading and motion. Accordingly, an annulus fibrosus repair patch (AFRP); a collagen-based multi-laminate scaffold with an angle-ply architecture has been previously developed, which demonstrates similar mechanical properties to native outer AF (oAF). To further enhance the mimetic nature of the AFRP, interlamellar (ILM) glycosaminoglycan (GAG) was incorporated into the scaffolds. The ability of the scaffolds to withstand simulated impact loading and resist herniation of native IVD tissue while contributing to the restoration of spinal kinematics were assessed separately. The results demonstrate that incorporation of a GAG-based ILM significantly increased (p<0.001) the impact strength of the AFRP (2.57 ± 0.04 MPa) compared to scaffolds without (1.51 ± 0.13 MPa). Additionally, repair of injured functional spinal units (FSUs) with an AFRP in combination with sequestering native NP tissue and a full-thickness AF tissue plug enabled the restoration of creep displacement (p=0.134), short-term viscous damping coefficient (p=0.538), the long-term viscous (p=0.058) and elastic (p=0.751) damping coefficients, axial neutral zone (p=0.908), and axial range of motion (p=0.476) to an intact state. Lastly, the AFRP scaffolds were able to prevent native IVD tissue herniation upon application of supraphysiologic loads (5.28 ± 1.24 MPa). Together, these results suggest that the AFRP has the strength to sequester native NP and AF tissue and/or implants, and thus, can be used in a composite repair strategy for IVDs with focal annular defects thereby assisting in the restoration of spinal kinematics.